Diagnostic Accuracy of Surgeon-Led Ultrasound Guided Lung Biopsy In Suspected Thoracic Malignancy - Adhikari, Mahesh Mani; Thakur, Binay; Khatiwada, Sagar; Tiwari, Manoj; Kharel, Ashish; Bhattarai, Shachee; Sapkota, Sandeep; Raut, Saujan (Nepalese Journal of Cancer, 2026)
Background: Lung cancer is the leading solid organ malignancy in the world, having the highest share of financial burden in the world population. Increasing lung cancer patients can result in increase in waiting time for early diagnosis and treatment resulting in adverse outcome. Ultrasound guided lung and thoracic core needle biopsies done by non-radiologist clinicians are shown to reduce the waiting time for early diagnosis making the patient care efficient and safe. This study aimed to evaluate the diagnostic accuracy of surgeon led point-of-care ultrasound (POCUS) guided thoracic core needle biopsies for suspected thoracic malignancies in Nepal.Methodology: This study evaluated 226 patients retrospectively, who underwent POCUS guided thoracic core-needle biopsy at our institution from September 2023 to January 2025. All the biopsy reports available were collected retrospectively and descriptive analysis done.Results: The diagnostic yield of the surgeon led POCUS thoracic biopsy was 94.7%, 4.4% required repeat biopsy and radiological correlation was advised in 0.9%. Squamous cell carcinoma of the lung (28.3%) was the most common histological diagnosis made in the biopsies. Five cases (2.21%) developed pneumothorax after the core needle biopsy among which two required pigtail chest drain.Conclusion: Surgeon-led POCUS thoracic biopsies can be done safely increasing the diagnostic efficiency of the institution resulting in reduction in waiting time and reducing the patient load in radiology suit for the same procedure.